Comparison of the First and Second Wave of Infections by SARS-CoV-2: A Retrospective and Longitudinal Study From a Primary Health Care Center in Santiago of Chile - Acuña-Castillo, Claudio; Inostroza-Molina, Ailen; Castro, Sergio A.; Molina-Cabrera, Sonia; Leiva-Salcedo, Elías; Riquelme, Denise; Luraschi, Roberto; Barrera-Avalos, Carlos; Vallejos-Vidal, Eva; Mella-Torres, Andrea; Valdés, Daniel; Torres, Claudio; et al. (Frontiers in Public Health, 2022)
The current COVID-19 pandemic is caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Many countries have reported the experience of at least two contagion waves, describing associated mortality rates and population behavior. The analysis of the effect of this pandemic in different localities can provide valuable information on the key factors to consider in the face of future massive infectious diseases. This work describes the first retrospective and comparative study about behavior during the first and second waves of the COVID-19 pandemic in Chile from a primary Healthcare Center. From 19,313 real-time quantitative PCR (RT-qPCR) tests assessed, the selected 1,694 positive diagnostics showed a decrease in mortality rate in the second wave (0.6%) compared with the first (4.6%). In addition, we observed that infections in the second wave were mainly in young patients with reduced comorbidities. The population with a complete vaccination schedule shows a decrease in the duration of symptoms related to the disease, and patients with more comorbidities tend to develop severe illness. This report provides evidence to partially understand the behavior and critical factors in the severity of the COVID-19 pandemic in the population of Santiago of Chile.